Increasing the Accuracy of Assessment of Soil Subsidence for the Safe Processing of Pipelines - Eminov, R.A.; Mammadova, S.B.; Aliyarova, X.E. (Herald of Azerbaijan Engineering Academy, 2025)
It is shown that monitoring of soil subsidence in pipeline laying zones is a necessary measure to ensure its safe operation, and the widespread use of differential interferometric aperture radars (InSAR) for these purposes is noted. It has been established that such components of the InSAR radio wave delay as hydrostatic ∆Lhyd and wet ∆Lwet delays can be minimized by ensuring a certain pattern of relationship between the indicators of height H and geographic latitude φ of the surface. A condition is determined for ensuring joint minimization of the components ∆Lhyd and ∆Lwet while ensuring a single relationship between H and φ.